An endogenous DNA adduct as a prognostic biomarker for hepatocarcinogenesis and its prevention by Theaphenon E in mice. Issue 1 (13th November 2017) - Fu, Ying; Silverstein, Shana; McCutcheon, Justine N.; Dyba, Marcin; Nath, Raghu G.; Aggarwal, Monika; Coia, Heidi; Bai, Angela; Pan, Jishen; Jiang, Jiji; Kallakury, Bhaskar; Wang, Hongkun; et al.
Abstract : Hepatocellular carcinoma (HCC) is the third leading cause of cancer–related deaths worldwide, mainly because of its poor prognosis. A valid mechanism‐based prognostic biomarker is urgently needed. γ‐hydroxy‐1, N 2 ‐propanodeoxyguanosine (γ‐OHPdG) is an endogenously formed mutagenic DNA adduct derived from lipid peroxidation. We examined the relationship of γ‐OHPdG with hepatocarcinogenesis in two animal models and its potential role as a prognostic biomarker for recurrence in HCC patients. Bioassays were conducted in xeroderma pigmentosum group A knockout mice and diethylnitrosamine‐injected mice, both prone to HCC development. γ‐OHPdG levels in the livers of these animals were determined. The effects of antioxidant treatments on γ‐OHPdG and hepatocarcinogenesis were examined. Using two independent sets of HCC specimens from patients, we examined the relationship between γ‐OHPdG and survival or recurrence‐free survival. γ‐OHPdG levels in liver DNA showed an age‐dependent increase and consistently correlated with HCC development in all three animal models. Theaphenon E treatment significantly decreased γ‐OHPdG levels in the liver DNA of xeroderma pigmentosum group A knockout mice and remarkably reduced HCC incidence in these mice to 14% from 100% in the controls. It also effectively inhibited HCC development in the diethylnitrosamine‐injected mice. Using clinical samples from two groups of patients, our study revealed that higher levels of γ‐OHPdG are strongly associated with low survival ( P < 0.0001) and low recurrence‐free survival ( P = 0.007). Conclusion: These results support γ‐OHPdG as a mechanism‐based, biologically relevant biomarker for predicting the risk of HCC and its recurrence. (Hepatology 2018;67:159‐170).